Climate change mitigation and food loss and waste reduction: Exploring the business case - Gromko, Duncan; Abdurasulova, Gulbahar (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The carbon footprint of food loss and waste (FLW) is estimated to be up to 3.49 gigatons of carbon dioxide equivalent (gtCO2e), representing up to 6–10% of total anthropogenic greenhouse gas (GHG) emissions (HLPE 2014). Addressing FLW can reduce the emission intensity of the agricultural system; i.e. the number of tons of GHG emissions per ton of food consumed. This is critical, as global demand for food continues to rise. In addition to climate change mitigation, there are environmental, social, and economic benefits associated with reducing FLW. While development organizations have long promoted FLW measures, commercial uptake of FLW interventions lags in many developing countries. Supply chain analysis can identify opportunities for profitably reducing FLW. This study examines the business case for reducing FLW in three supply chains: dairy in Kenya, cereals in Tanzania, and tomatoes in Nigeria.